First order dynamics approaching of broiler chicken deep body temperature response to step changes in ambient temperature - Hamrita, Takoi K; Conway, Richard H. (International Journal of Agricultural and Biological Engineering, 2017)
Traditional environmental control methods for poultry housing which rely solely on environmental factors fall short in meeting thermal and physiological needs of the animals. New methods are needed that factor in the physiological needs and responses of the animals in order to maximize well-being of the animals and minimize heat stress. Deep body temperature (DBT) has been shown in the literature to be a strong indicator of heat stress, therefore studies are needed that help us gain a deeper understanding of the relationship between this variable and environmental conditions. The aim of this study was to identify the order of the dynamic response of poultry DBT to large step changes in ambient temperature (AT). Temperature steps had to be big enough to take the chickens out of their homeothermic zone. A total of 46 DBT/AT data sets with 23 upward AT steps and 23 downward AT steps were obtained using a biotelemetry system, and involving three chickens. DBT responses of individual chickens to step changes in AT were found to have a 0.88 average Pearson correlation suggesting consistency in chickensï¿½ responses to the same stimuli (p < 0.0005). The data indicated that DBT responses to AT followed a first order behavior in most cases with an average time constant of 1.6 h, and the curve fitting method was used to validate this observation. There was a 0.88 average correlation between DBT model and measured data (p < 0.0005). These results indicate statistical significance in the data used and the model derived from it. In conclusion, it is reasonable to assume that the dynamic response of poultry DBT to large step changes in ambient temperature follows a first order model. Although further studies are needed to more fully derive the model, this study provided a stepping-stone towards gaining a better understanding of the relationship between DBT and AT, therefore taking us one step closer towards making optimal management and risk assessment decisions that are based on physiological needs of the chickens.Keywords: environmental control, ambient temperature, deep body temperature, biotelemetry, step response, dynamic modeling, broiler chicken, physiological responsesDOI: 10.25165/j.ijabe.20171004.2336Citation: Hamrita T K, Conway R H. First order dynamics approaching of broiler chicken deep body temperature response to step changes in ambient temperature. Int J Agric & Biol Eng, 2017; 10(4): 13-21.